2011
DOI: 10.1089/ten.tea.2010.0395
|View full text |Cite
|
Sign up to set email alerts
|

High Amplitude Direct Compressive Strain Enhances Mechanical Properties of Scaffold-Free Tissue-Engineered Cartilage

Abstract: Adult cartilage has a limited healing capacity. Damages resulting from disease or injury increase over time and cause severe pain. One approach to reinstate the cartilage function is tissue engineering (TE). However, the generation of TE cartilage is time consuming and expensive and its properties are so far suboptimal. As in vivo cartilage is subject to loading, it is assumed that mechanical stimulation may enhance the quality of TE cartilage. In this study the short-term influence of variable compressive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 62 publications
0
31
0
1
Order By: Relevance
“…Mechanical stimulation of scaffold-free and self-assembled tissue has also shown promising results [229, 232, 238]. Self-assembled articular cartilage has been shown to withstand hydrostatic pressures of up to 10 MPa and respond positively by increasing aggregate modulus (96%), Young's modulus (92%), collagen per wet weight (51%) and GAG per wet weight (52%) [235].…”
Section: Scaffoldless Self-assembly Of Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Mechanical stimulation of scaffold-free and self-assembled tissue has also shown promising results [229, 232, 238]. Self-assembled articular cartilage has been shown to withstand hydrostatic pressures of up to 10 MPa and respond positively by increasing aggregate modulus (96%), Young's modulus (92%), collagen per wet weight (51%) and GAG per wet weight (52%) [235].…”
Section: Scaffoldless Self-assembly Of Tissuementioning
confidence: 99%
“…Self-assembled articular cartilage has been shown to withstand hydrostatic pressures of up to 10 MPa and respond positively by increasing aggregate modulus (96%), Young's modulus (92%), collagen per wet weight (51%) and GAG per wet weight (52%) [235]. A somewhat similar study of scaffold-free porcine chondrocyte constructs demonstrated beneficial responses to direct compression stimulation at strain amplitudes of 5-20% [229]. Following this loading, 200-300% increases in construct stiffness and a 250% increase in Young's modulus was measured [229].…”
Section: Scaffoldless Self-assembly Of Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…A stress-strain profile was obtained from the load and displacement data at the end of each relaxation phase to determine the unconfined compressive modulus [39].…”
Section: Mechanical Properties Of Printed Scaffoldmentioning
confidence: 99%
“…Fonksiyonel kıkır-dak, fibrokartilaj ve diğer dokuların oluşumu için uygun olduğu görülmüştür. [67][68][69][70] Self-assembly bu yüzden TME disk doku mühendisliği için bir alternatif olabilir ve uygulanabilir, fakat yapı iskelesi olmayan yapıların hücrelerin yaşanabilirliliğini destekleme ve matriks üretimi konusunda yetersiz olduğu görülmüştür.…”
Section: Yapı ġSkelesi ġçErmeyen Sistemlerunclassified